Budżetowanie kosztów na przykładzie przedsiębiorstwa produkcyjnego "BETA". Problemy powstałe w trakcie wdrażania systemu budżetowania - Knihnicka, Joanna (Cost budgeting on the example of productive enterprise beta. Problems formed during implementation, 2006)
Budgeting in business activities is one of the most important tools in management. The main goal of budgeting in a company is the assurance of effective location of limited resources, that the company have. We have to know that efficiency of budgeting depends on many factors an enterprise.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1125, s. 68-72